'Citizens' in foreign policy theorising: President Yar'Adua and Nigeria's citizen diplomacy. Issue 4 (2nd October 2021) - Oshewolo, Segun
ABSTRACT: The link between citizens and international diplomacy has received attention in foreign policy theorising. As a participant in the diplomatic process, the individual/citizen is closely connected to diplomacy and its outcome. While he is expected to be involved in the crafting and framing of foreign policy choices and their attendant diplomatic instruments, he is also the object of diplomacy as the ultimate goal of diplomacy is to promote his well-being. The managers of Nigeria's foreign relations in the Ministry of Foreign Affairs under President Umar Musa Yar'Adua adopted the foreign policy thrust of citizen diplomacy to address the problems confronting Nigerian citizens at home and abroad. Although the crafting of the policy was a welcome development, there were critical issues involved in its implementation. The study observes that the pursuit of the policy was hampered by poor articulation of the policy and general abysmal exposition of diplomacy in the context of Nigeria, poor budgetary allocation to the Ministry of Foreign Affairs, and the lack of 'full' citizenship considered sacred and inviolable by the Nigerian state. These encumbrances must be addressed if the policy must yield the anticipated dividends in the post-Yar'Adua era.